Women’s Perceptions of Graduate Level Educational Administration Programs - Epp, Juanita Ross (Canadian Journal of Higher Education, 1994)
Women in graduate programs have, in the past, been subject to a "chilly climate" (Hall & Sandler, 1982). Those in educational administration faced particular problems associated with the male orientation of the discipline (Edson, 1988). Has this diminished now that half of the students are women? Although there were many positive reports, the overall experiences for women in educational administration programs were often marred by discriminatory attitudes displayed by specific professors, negative responses to affirmative action initiatives voiced by fellow students, and resentment displayed by both male professors and male students toward female professors. In the students' perceptions, universities had done little to encourage women, although some had been able to take educational administration courses intended to address issues of gender or women's studies courses as part of program. Positive experiences were often associated with exposure to women mentors interested in qualitative research methods. Students' recommendations for improvement of educational administration programs centred around the inclusion of women in course content, the "upgrading " of particularly entrenched professors, and program changes to provide more flexibility. Students were also concerned with changing the school systems themselves, in order to improve job opportunities once they had completed their programs.